Spatiotemporal patterns of urban expansion and trade-offs and synergies among ecosystem services in urban agglomerations of China. (April 2023) - Tian, Peng; Liu, Yongchao; Li, Jialin; Pu, Ruiliang; Cao, Luodan; Zhang, Haitao
Highlights: China's urban agglomeration is rapidly expanding in an edge-expansion type. Various ecosystem services in China's urban agglomerations present a negative synergistic relationship. Urban agglomerations at different level varied in the synergy and trade-off relationship. Abstract: Urbanization is advancing rapidly across the globe, and urban agglomeration (UA) has become an important by-product of urbanization expansion. The rapid development of UAs has profound impacts on land use and directly affects various regional ecosystem services (ES). Understanding these impacts in UAs with developed economies and fragile ecosystems can help decision-makers formulate ecological protection and land use planning policies. Here, we selected 13 UAs in eastern, central, and western China and analyzed the characteristics of spatiotemporal changes in built-up land and the trade-off and synergy between ES in UAs from 2000 to 2020. We found that the built-up land increased rapidly to the outer edge of a city in the form of edge expansion, which was more prominent in UAs at national and regional scales. Carbon storage, biodiversity conservation, habitat quality, soil and water conservation, and water conservation tended to decrease, but the nutrition delivery ratio and food supply tended to increase. Various ES presented a negative synergistic relationship. The difference in ES in UAs was closely related to the level of urbanization and geographical location. Our findings demonstrate the trade-off and synergy of ES in UAs at different levels and can be used to sustain ES and develop high-quality UAs.